An Efficient IoT-Based Novel Approach for Fire Detection Through Esp 32 Microcontroller in Forest Areas - Subbarayudu Yerragudipadu; Vijendar Reddy Gurram; Bhargavi Jammi; Latha Kadavath (MATEC Web of Conferences, 2024)
Forest fires have become a major threat these days. The hazard posed by forest fires has increased globally. It has a detrimental effect on both human and forest ecosystems. Forest fires can be due to natural changes such as changes in the climate and the Greenhouse effect is due to human activities. Human activities are the major reason for forest fires interestingly. It is important to spot the fires early to reduce the major destruction and loss. In this project, we have proposed a system and methodology which is a wireless sensor network to identify forest fires in early stage. Our project will help to detect the fire in the early stage by using the sensor and intimate through a buzzer and a message to the administration of the forest, therefore the immediate necessary actions can be taken in time and can stop the fire. Administrative officers are constantly monitored. This system has many benefits and protects the environment, forest survivors, infrastructure, lives, and ecosystem. Saving our environment is a major thing in this developing country and world. Forest fire is a biggest natural and man-made calamity int he world. It’s a environment tragedy. Once the fire is not detected and it spreads over a huge area destroying everything, such destruction should be avoided and should save our forest habitats effort of this project is to create and implement a IoT based system that can sense and detect forest fires in early and notify to the responsible officials.